Dasar Hukum Pengajuan Peninjauan Kembali yang Dilakukan Oleh Kejaksaan - Reni Halida Malik (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2023)
The development of the community's need for legal renewal has given rise to many legal phenomena that have emerged at this time. One of them is the submission of legal action for Judicial Review (PK/Heirziening) which is submitted by the prosecutor, even though so far the public sees and knows that legal action for Judicial Review (PK)/Heirziening can only be submitted by the convict, his legal advisor or his heirs. This is clearly regulated in the Indonesian Criminal Procedure Law (KUHAP) that the legal action for Judicial Review (PK)/Herziening is carried out by the convict (can also be submitted through his legal advisor) or his heirs. The legal action for Judicial Review (PK)/Herziening by prosecutors has been carried out repeatedly in Indonesia , and the Chief Justice at the Supreme Court has several times granted the prosecutor's judicial review (PK)/Herziening. The formulation and historical background of the Criminal Procedure Code is clear that PK is the right of the convict or his heirs. The PK requested by the prosecutor has so far violated the regulations legislation. The Criminal Procedure Code does not at all mention that prosecutors can apply for PK, historically PK is actually given as a last resort to the convict or his heirs to change his 'fate'.